Bone Tissue Engineering: A Biphasic Osteovascular Biomimetic Scaffold for Rapid and Self‐Sustained Endochondral Ossification (Adv. Healthcare Mater. 13/2021). Issue 13 (9th July 2021) - Kim, Hwan D.; Hong, Xuechong; An, Young‐Hyeon; Park, Mihn Jeong; Kim, Do‐Gyoon; Greene, Arin K.; Padwa, Bonnie L.; Hwang, Nathaniel S.; Lin, Ruei‐Zeng; Melero‐Martin, Juan M.
Abstract : In article number 2100070, Juan M. Melero‐Martin, Ruei‐Zeng Lin, and co‐workers present a biphasic scaffold that allows self‐sustained endochondral ossification. Following seeding with human vascular and mesenchymal stem cells, this biomimetic material enables the rapid generation of osteovascular niches and ossification centers, leading to the formation of vascularized bone tissue in vivo.